Penerapan european foundation for quality management’s (efqm) excellence model pada sistem pengukuran kinerja jurusan Teknik Mesin Universitas Udayana - Penindra, I Made Dwi Budiana (Jurnal Energi Dan Manufaktur, 2018)
Abstrak Globalisasi merupakan fenomena yang tidak dapat dihindari dalam tata kehidupan kita dimana persaingan antar negara semakin terbuka terutama pada bidang sumber daya manusia. Untuk menghadapi keadaan tersebut maka perguruan tinggi diharapkan menjadi pusat penyelenggaraan dan pengembangan pendidikan tinggi yang menghasilkan manfaat dan meningkatkan mutu kehidupan bermasyarakat, berbangsa dan bernegara. Jurusan Teknik Mesin adalah salah satu jurusan yang telah mendapatkan akreditasi A dari BAN PT dimana saat ini baru 20% jurusan yang terakreditasi di lingkungan Unuversitas Udayana. Didalam meningkatkan kinerja perlu kiranya dirancang suatu sistem pengukuran kinerja yang terintegrasi dimana saat ini Jurusan Teknik Mesin belum memiliki sistem pengukuran kinerja yang baik. Dalam menyempurnakan sistem pengukuran kinerja yang telah ada, maka akan dilakukan Analisis, perancangan dan implementasi sistem pengukuran kinerja dengan European Foundation for Quality Management’s (EFQM) Execellence Model dimana metode tersebut diintregasikan dengan beberapa metode yaitu Metode Objectives Matrix (OMAX), Integrated Performance Measurement Systems (IPMS), dan Analytical Hierarcy Process (AHP) pada Jurusan Teknik Mesin Universitas Udayana. Langkah-langkah atau rincian dari metode penelitian yang diharapkan adalah mengikuti tahapan sebagai berikut : Pemilihan Metode Pengukuran Produktivitas, Jenis dan Metode Pengumpulan Data, Identifikasi Indikator-Indikator atau Kriteria Produktivitas yang Akan Diukur, Pemberian Bobot Dari Masing-Masing KPI Yang Diukur, Pengolahan Data Atau Pengukuran Kriteria Produktivitas, Evaluasi Produktivitas. Dari hasil penelitian dapat disimpulkan bahwa Implementasi Sistem Pengukuran Kinerja dengan European Foundation for Quality Management’s (EFQM) Execellence Model yang diintegrasikan Integrated Performance Measurement Systems (IPMS) dan Metode Objectives Matrix (OMAX) memiliki perbedaan pandangan pada penentuan stakeholder requirement, dari 40 stakeholder requirement dijabarkan menjadi 15 KPI. Implementasi pada semester genap 2014/2015 menunjukkan peningkatan sebesar 83,92 % dari periode sebelumnya dengan Indeks Performance Indicator sebesar 773,35. Kata kunci: Pengukuran kinerja, European Foundation for Quality Management’s (EFQM) Execellence Model, Metode Objectives Matrix (OMAX), Integrated Performance Measurement Systems (IPMS), dan Analytical Hierarcy Process (AHP) Abstract Globalization is a phenomenon that can not be avoided in the governance of our lives where competition between countries become more open, especially in the field of human resources. To deal with the situation, the college is expected to be the center of the implementation and development of higher education that generate benefits and improve the quality of life of society, nation and state. Department of Mechanical Engineering is one of the departments that have earned accreditation from BAN PT where currently only 20% of accredited departments in the university. In order to improve its performance, it would need to design an integrated performance measurement system which is now the Department of Mechanical Engineering has not had a good performance measurement system yet. Enhancing performance measurement systems that already exist, analysis, design and implementation of performance measurement system will be done with the European Foundation for Quality Management's (EFQM) excellence model wherein the method is integrated by several methods, namely Methods Objectives Matrix (OMAX), Integrated Performance Measurement Systems (IPMS), and Hierarcy Analytical Process (AHP) in the Department of Mechanical Engineering University of Udayana. Steps or details of the research methods to be expected is as following steps: Selection Method of Measuring Productivity, Types and Data Collection Methods, Identification Indicators or the Criterion productivity will be measured, Giving Weights From Each KPI The Measured, Data Processing or Measurement Criteria Productivity, Productivity Evaluation. The results of this research concluded the implementation of Performance Measurement System with the European Foundation for Quality Management's (EFQM) excellence model integrated Integrated Performance Measurement Systems (IPMS) and Methods Objectives Matrix (OMAX) have differing views on the determination of stakeholder requirements, from 40 stakeholder requirements outlined to 15 KPI. Implementation of the second semester of 2014/2015 showed an increase of 83.92% from the previous period with Performance Indicator index of 773.35 Keywords: Productivity Measurement, European Foundation for Quality Management's (EFQM) excellence model integrated Integrated Performance Measurement Systems (IPMS) and Methods Objectives Matrix (OMAX), dan Analytical Hierarcy Process (AHP)